Theory Model of Planning Behavior in Explaining Dieting Behavior in Obese Women - Poppy Dewi Ratih; Noor Rochman Hadjam; Ria Maria; Karmilasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Obesity has been a threat to humans for a long time. The increase in the number of sufferers has started to worry. The fact is that in almost all regions, women have a higher prevalence of obesity than men. It takes a physical intervention to end obesity, one form is diet. This study aims to look at dietary behavior in first-degree obese women as explained by the theory of planned behavior (TPB) model in obese women. The sample in this study used non-probability sampling with a purposive sampling technique. The criteria imposed on the respondents of this study were, women, with first-degree obesity, went on a diet with professional assistance, namely nutrition specialists. The results in this study indicate that the theory of planned behavior model can be constructed to see dietary behavior in obese women, which means that this theoretical model fits between the data in the field and theory